Identification, Localization, and Quantification of HIV Reservoirs Using Microscopy. Issue 1 (28th September 2018) - Prevedel, Lisa; Ruel, Nancy; Castellano, Paul; Smith, Carla; Malik, Shaily; Villeux, Courtney; Bomsel, Morgane; Morgello, Susan; Eugenin, Eliseo A.
Abstract: The major barrier to eradicating human immunodeficiency virus‐1 (HIV) infection is the generation and extended survival of HIV reservoirs. In order to eradicate HIV infection, it is essential to detect, quantify, and characterize circulating and tissue‐associated viral reservoirs in infected individuals. Currently, PCR‐based technologies and Quantitative Viral Outgrowth Assays (Q‐VOA) are the gold standards to detect viral reservoirs. However, these methods are limited to detecting circulating viral reservoirs, and it has been shown that they misrepresent the size of the reservoirs, largely because they detect only one component of the HIV life cycle and are unable to detect viral reservoirs in tissues. Here, we described the use of multiple detection systems to identify integrated HIV DNA or viral mRNA and several HIV proteins in circulating and tissue reservoirs using improved staining and microscopy techniques. We believe that this imaging‐based approach for detecting HIV reservoirs will lead to breakthroughs necessary to eradicate these reservoirs. © 2018 by John Wiley & Sons, Inc.